Production and electrolysis of light metals : proceedings of the International Symposium on Production and Electrolysis of Light Metals, Halifax, August 20-24, 1989 - Closset, B. de (Bernard) (Proceedings of the Metallurgical Society of the Canadian Institute of Mining and Metallurgy, 1989)
Production and electrolysis of light metals - smelter operations, aluminum casting, aluminum melt treatment and control, electrolysis of light metals: magnesium and aluminum. Electrolysis of light metals: lithium, titanium and gallium. Reduction and production of light metals.